Implementasi Teori Akuntansi Dalam Perumusan Standar Akuntansi Pelaporan Keuangan - Siti Nur Adillah; Cici Putri Ardyanti; Nurlaila Nurlaila (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
At the beginning, accounting was merely a very simple record-keeping. It was only to record the economic transactions happened in the society at that time. Along with the breakthrough period and human needs in every transaction, the basic clear rules are keenly needed that can be tailored to the development of technological progress. Due to such rationale, an accounting theory is needed to answer all hypotheses on the phenomena that occurs in the society. The thinkers and researchers in the field of accounting continue to work with various methods and approaches to implement the accounting theory which is acceptable by all users of the accounting community in the world and so as to produce a Statement of Basic Accounting Theory (ASOBAT) published by the AAA in 1966 and Positive Accounting Theory (PAT) appeared in 1979. Outlining the process of formulation of accounting theory, the emergence of ASOBAT and PAT and finding the reason of accepting the accounting standards in the world (IASC-IFRS) is the purpose of writing this paper.